Educación tributaria y financiera en estudiantes del 5to secundaria de la I.E.P. Rosa de América distrito de Iquitos periodo 2023 - Alado Macanilla, Gina Gabriela (2024)
The present Study entitled Tax and financial education in 5th secondary students of the I.E.P Rosa de América, Iquitos district, period 2023, was carried out with the objective of determining the level of tax and financial education in students of the I.E.P. Rosa de América District of Iquitos period 2023, so a descriptive type of research, with a non-experimental design, was chosen, where 60 students from the 5th secondary school who voluntarily decided to participate in this research work were taken as the study population. who were surveyed and responded to a properly structured questionnaire; According to the analysis of the results obtained, it was determined that 77.8% have a high level of financial education, while 22.2% have a low level of financial education and 73.4% have a high level of tax education, while 26.6% have a high level of tax education. % have a low level of tax education, it is concluded that the level of financial and tax education in 5th year high school students of the I.E.P. Rosa de América District of Iquitos Period 2023 is of medium level.